Visitor's satisfaction towards facilities in Perdana Botanical Garden, Kuala Lumpur - Abdul Manan, Syakir Junaidi (2016)
Visitor’s satisfaction towards the facilities provided is important for the management in order to satisfy visitors in Perdana Botanical Garden. This study was conducted in order to determine visitor’s satisfaction towards facilities in Perdana Botanical Garden and also to determine the influencing factors towards visitor’s satisfaction in the area. A questionnaire together with a convenience sampling technique was used to collect this data in this study. Visitors were most satisfied with the attractive view of the surrounding with the highest mean which is 4.28. There was only one facility that showed low mean of satisfaction which is food stall provide in the park area. So we considered this as a small problems faced by the management of the park area. In general, facilities provided in this park were performed well. Based, on the results, we can see the facilities that visitors satisfied or unsatisfied and also which facilities need an action for upgrading their performances.